Lehdia Mohamed Dafa and the Gendered Borders in Hispano-Saharawi Literature - Odartey-Wellington, Dorothy (Revista Canadiense de Estudios Hispánicos, 2022)
Women from the Saharawi Arab Democratic Republic (SADR) are often portrayed as symbols of Saharawi sovereignty and identity. However, there is a growing echo of voices against the conflation of women and the Saharawi nation. Drawing on border poetics and postcolonial feminist criticism, this essay analyzes the ways in which Hispano-Saharawi writer Lehdia Mohamed Dafa challenges the boundaries of the Saharawi nation that are symbolically traced with, and upon, women’s bodies. It also examines the ways in which Mohamed Dafa departs from the notion of Saharawi women as emblems of nationhood and, instead, reimagines them as citizens with differentiated identities.